Magnetic Resonance Imaging - Manchev, Lachezar (IntechOpen, 2019)
Diagnostic imaging has undergone many changes over the last several years. Technical developments have defined Magnetic Resonance Imaging (MRI) as the leading diagnostic modality in different diseases. MRI is definitive and sensitive and the current requirements of medicine call for radiologists to be proficient in its use. This book provides complete and detailed information about the fast-developing field of MRI from physicians, radiologists, and other clinical specialists. It is a practical guide to using MRI in areas such as cardiology and pulmonology, among others.